Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian HP Android Di Surabaya - Shandi Buana Azis; Priyo Utomo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims (1)to answer and analyze how product quality influences segmental purchasing decisions, (2)to answer and analyze how price influences segmental purchasing decisions, (3)to answer and analyze how promotion influences segmental consumer buying decisions, and (4)to answer and analyze the influence of product quality, price, and promotion on purchasing decisions simultaneously. The population of this study is customers who acquired Android mobile phones during the past six months in Surabaya in 2022 with a sample size of 150 respondents based on the incidental sampling method. Technique for gathering data that involves distributing surveys with a Likert scale. The data analysis tools are the traditional assumption tests (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression test, hypothesis test (t-test and f-test), and test the coefficient of determination using SPSS. The results of this study indicate that product quality has a good and substantial effect on segmental purchasing decisions, price has a good and substantial effect on segmental purchasing decisions, and promotion has a good and substantial effect on segmental purchasing decisions. Simultaneously, product quality, price, and promotion have a substantial and positive effect on purchasing decisions. Product quality, price, and promotions on Android phones have a big influence on purchasing decisions.